Correlation between RAGE gene promoter methylation and diabetic retinal inflammation - Kan, Shifeng (Exp Ther Med, 2018)
The methylation status of the receptor for advanced glycation end products (RAGE) gene promoter in peripheral blood mononuclear cells (PBMCs) of type 2 diabetic retinopathy (DR) patients was evaluated to investigate the correlation between RAGE gene promoter methylation and diabetic retinal inflammation. Eighty patients admitted and diagnosed as type 2 DR in Qilu Hospital, Shandong University during the period from October, 2013 to October, 2015 were enrolled in this study. They were the observation group and 40 healthy subjects were enrolled in the control group. PBMCs were collected from patients using density gradient centrifugation, and the methylation status of RAGE gene promoters was detected using methylation-specific PCP (MSP). Interleukin-1β (IL-1β), IL-6 and tumor necrosis factor-α (TNF-α) levels of in the serum were measured using enzyme-linked immunosorbent assay (ELISA). PBMCs in patients with positive RAGE gene promoter methylation were isolated and cultured and RAGE gene promoter methylation was inhibited using the demethylating agent, 5′-aza-2′-deoxycytidine (5-aza-dC). The methylation status of RAGE gene promoters in PBMCs was detected via MSP. IL-1β, IL-6 and TNF-α levels in the supernatant of PBMC culture solution were evaluated using ELISA. MSP results showed that there were 26 cases (32.50%) of RAGE gene promoter methylation in PBMCs in DR patients. RAGE gene promoters were methylated in all normal healthy subjects. IL-1β, IL-6 and TNF-α levels in serum for positive RAGE gene promoter methylation group were significantly lower than those in negative RAGE gene promoter methylation group (p<0.01). 5-aza-dC inhibited the RAGE gene promoter methylation of PBMCs in patients with positive RAGE gene promoter methylation. The inhibition of methylation in RAGE gene promoter increased the levels of IL-1β, IL-6 and TNF-α in supernatant of culture solution. In conclusion, RAGE gene promoter hypomethylation was detected in DR patients, indicating that RAGE gene promoter methylation could inhibit the diabetic retinal inflammation.